2020
DOI: 10.1186/s41601-020-00163-x
|View full text |Cite
|
Sign up to set email alerts
|

Power quality enhancement and engineering application with high permeability distributed photovoltaic access to low-voltage distribution networks in Australia

Abstract: Considering power quality problems such as overvoltage and three-phase unbalance caused by high permeability distributed photovoltaic access in low-voltage distribution networks, this paper proposes a comprehensive control scheme using a static var. generator (SVG), electric energy storage (EES), a phase switching device (PSD) and an intelligent terminal controller. The control strategies of transformer overload, bus over/under voltage, anticountercurrent, storage battery state of charge (SOC) maintenance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…A 250 kW PV system under this study is mainly composed of a power transformation system and a control system (Aouchiche, 2020). The former system includes seven components, i.e., PV array, boost converter, three-phase inverter, filter, transformer, grid, and load while the latter one is divided into maximum power point tracking (MPPT) control and inverter control (Li et al, 2020), shown in Figure 1. In addition, the perturbation observation (P and O) method is used to implement MPPT control while voltage regulator, current regulator as well as PLL controller accomplish precise and fast three-phase inverter control through coordinate and efficient cooperation.…”
Section: Grid-connected Pv Systemmentioning
confidence: 99%
“…A 250 kW PV system under this study is mainly composed of a power transformation system and a control system (Aouchiche, 2020). The former system includes seven components, i.e., PV array, boost converter, three-phase inverter, filter, transformer, grid, and load while the latter one is divided into maximum power point tracking (MPPT) control and inverter control (Li et al, 2020), shown in Figure 1. In addition, the perturbation observation (P and O) method is used to implement MPPT control while voltage regulator, current regulator as well as PLL controller accomplish precise and fast three-phase inverter control through coordinate and efficient cooperation.…”
Section: Grid-connected Pv Systemmentioning
confidence: 99%
“…The simulation of three-phase bolted three-phase shortcircuits currents per IEC 60909 Standard. This study calculates initial symmetrical RMS, peak, symmetrical and asymmetrical breaking RMS, steady-state RMS short circuit currents and their DC offset at faulted nozzles as the basic system reference quantities approved in our previous article with a maximum value recorded in a three-phase bolted fault and defined as a model to be used and compared with the values obtained by the factory manufacturer with Different Load and Contingency Scenarios [19], all the important busses and those to be protected by main circuit breakers have been chosen as it allows the maximum current during the fault to be determined to determine the breaking and closing powers of the devices as well as the electromechanical and thermal behavior of the equipment of the devices and to calculate the settings of the protection relays and the fuse ratings, to ensure good selectivity [20][21][22].…”
Section: Simulation Of Short Circuit Analysismentioning
confidence: 99%
“…In recent years, for the purpose of reducing dependence on fossil fuels, the electric power structure needs to shift more toward renewables to facilitate energy transformation (Zhang et al, 2015;Hou et al, 2017;Meng et al, 2021). Consequently, renewables (Chen et al, 2018;Li et al, 2020;Pabitra and Abhik, 2020;Zhao et al, 2021a) (e.g., solar, wind, hydro energy, etc.) have been wildly developed around the world, upon which the wind energy is increasingly emerging as one of the most mature, promising, and representative renewables, thanks to its unique superior, i.e., clean, reproducible, stable, well-stocked (Liu et al, 2021), and widespread (Díaz and Guedes Soares, 2020).…”
Section: Introductionmentioning
confidence: 99%